Menggaet Lebih Banyak Tamu Francophones: Pembelajaran Bahasa Prancis bagi Warga dan Karyawan Kampung Homestay Borobudur - B.R. Suryo Baskoro; Hayatul Cholsy (Bakti Budaya: Jurnal Pengabdian kepada Masyarakat, 2018)
Learning French for residents and homestay employees in the homestay village, Dusun Ngaran, DesaBorobudur is carried out by the French Literature Study Program, Faculty of Cultural Sciences,UGM as a community service activity in 2018. Tis learning is a follow-up of French languagetraining for homestay owners who have done in 2017. Using a tutorial system in small groups andcommunicative approaches, residents and homestay employees have been able and feel confdent ingreeting, oﬀering, explaining, giving choices, and other verbal activities related to guests or potentialguests in French (francophones) through simple communicative expressions. Simple French languageskills are a powerful capital to attract more francophones guests to visit the homestays. Te supportof French Literature Study Program on tourism development in Borobudur Homestay Village wasalso given in the form of assistance in promoting the region's tourism potential through refnementof French language pages and brochures. Tus, francophones tourists can fnd out more easily andmore quickly their whereabouts and get to know the area in order to attract more tourists to stay ata homestay. Other results of this service are French language teaching materials in the form of textand documentary videos.